2020
DOI: 10.3390/agronomy10121931
|View full text |Cite
|
Sign up to set email alerts
|

Broomrape as a Major Constraint for Grass Pea (Lathyrus sativus) Production in Mediterranean Rain-Fed Environments

Abstract: Grass pea (Lathyrus sativus) is an annual legume crop that is currently underutilized but has the potential for reintroduction into Mediterranean rain-fed farming systems. In this study, we compared the adaptation of breeding lines in multi-environment field testing, which had wide variation for precocity, grain yield and broomrape infection. Heritability-adjusted genotype plus genotype-by-environment interaction (HA-GGE) biplot and non-metric multidimensional scaling (NMDS) were performed to determine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…We found that mild temperatures and rain were the climatic factors most influential on broomrape infection. Mild temperatures before crop flowering enhance broomrape seed germination and establishment, and rain and fresh temperatures at spring rain allows broomrape development and emergence [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…We found that mild temperatures and rain were the climatic factors most influential on broomrape infection. Mild temperatures before crop flowering enhance broomrape seed germination and establishment, and rain and fresh temperatures at spring rain allows broomrape development and emergence [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm this risk, but ranking second after the one of scenarios of excessive temperatures at grain filling. The use of very early maturing cultivars has been suggested to escape O. crenata in several legumes as precocity use to be correlated with reduced infection [46,47]. This could also help to escape from high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe and in particular, in the Southern regions, where a "Mediterranean" climate prevails, grass pea cultivation has suffered already a severe reduction during the last century [29,38]. However, there is a renewed interest to re-introduce this hardish crop into Mediterranean rainfed cropping systems where it can be an alternative to overcome the expected climate change impacts [11,39]. The "Mediterranean" climate is characterized by mild wet winters and warm to hot dry summers, with the annual rainfall occurring during the winter half-year [40].…”
Section: New Challenges and Opportunities Due To The Impacts Of Clima...mentioning
confidence: 99%